Giant congenital facial hemangiopericytoma. Myofibromatosis variation - Guillermo Hernández-Peredo Rezk; Pastor Escárcega-Fujigaki; Valeria Zeferino-Herrera; Maximiliano Chimalpopoca-Moreno; Ana Patricia Zamora-Romero; Celin Gutiérrez-Canencia; Gloria Molina-Rodríguez; Janet Narváez-Farfán; Haydee Vélez Blanco; Claudia Morales-Gutiérrez; José de Jesús Loeza-Oliva; Lorelei A. Galicia Alvarado; et al. (Elsevier, 2021)
Hemangiopericytomas (HPCs) are rare soft-tissue tumors, their presence on the head is rare. We describe the treatment for this tumor with the intention of contributing to the knowledge of the pathology, which was resolved by surgery. This tumor was detected on the infant's temporomalar region in utero through ultrasonography of the a 38-year-old primigravida mother. Cesarean section was programmed for week 37, and the newborn was a single alive male, orotracheal intubation was performed. The physical examination revealed a 10 × 8x5 cm broad base tumor on the right side of his face. Histopathological findings indicated infantile facial hemangiopericytoma, myofibromatosis variant. A tracheostomy was performed, compressing the mass obstructing the airways, and ensuring ventilation. This pathology was resolved by surgery. Sixteen months after surgery, the child evolved adequately without tumor relapse data. In this research, we observed de following risk factor for the mother age, place of birth and UTI during the 6th month of pregnancy. These tumors rarely occur, and must be diagnosed prenatally by ultrasound. The treatment involved surgical excision which its important found cleavage plane, for complete resection. Although prognosis is relatively favorable in this type of infantile tumors, a painstaking follow-up is recommendable.